2019
DOI: 10.21083/partnership.v14i2.5409
|View full text |Cite
|
Sign up to set email alerts
|

Response to: Schira, H. R., & Hurst, C. (2019). Hype or Real Threat: The Extent of Predatory Journals in Student Bibliographies. Partnership: The Canadian Journal of Library and Information Practice and Research, 14(1).

Abstract: This response addresses issues raised by the recent publication in Partnership by Schira & Hurst (2019) in their article Hype or Real Threat: The Extent of Predatory Journals in Student Bibliographies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Ở phía ngược lại, không ít học giả cho rằng mối quan tâm về các "predatory journal" đang bị thổi phồng quá mức, là một nỗ lực để làm mất uy tín của phong trào truy cập mở (OA) hoặc rằng cuộc thảo luận về các "predatory journal" thu hút sự chú ý khỏi các vấn đề mang tính hệ thống trong xuất bản học thuật truyền thống [20] và vẫn còn những thiếu sót về danh sách cũng như tiêu chí xác định một "predatory journal" [21]. Hơn nữa, cũng có những ý kiến cho rằng các ý kiến của Beall là chủ quan, không đủ minh bạch và tin cậy, cần phải điều chỉnh, và rằng ông đã góp làm mất uy tín của phong trào OA, đặc biệt là ở các nước đang phát triển [21].…”
Section: Khái Niệm "Predatory Journal" (Tạp Chí Săn Mồi)unclassified
“…Ở phía ngược lại, không ít học giả cho rằng mối quan tâm về các "predatory journal" đang bị thổi phồng quá mức, là một nỗ lực để làm mất uy tín của phong trào truy cập mở (OA) hoặc rằng cuộc thảo luận về các "predatory journal" thu hút sự chú ý khỏi các vấn đề mang tính hệ thống trong xuất bản học thuật truyền thống [20] và vẫn còn những thiếu sót về danh sách cũng như tiêu chí xác định một "predatory journal" [21]. Hơn nữa, cũng có những ý kiến cho rằng các ý kiến của Beall là chủ quan, không đủ minh bạch và tin cậy, cần phải điều chỉnh, và rằng ông đã góp làm mất uy tín của phong trào OA, đặc biệt là ở các nước đang phát triển [21].…”
Section: Khái Niệm "Predatory Journal" (Tạp Chí Săn Mồi)unclassified
“…Others have focused on the degree to which predatory journals have the ability to undermine the scholarly record, academics, institutions, and their ability to influence patient care in clinical settings [ 13 - 19 ]. On the opposite end of the spectrum, some commentators have suggested that concerns over predatory journals are over-blown, are an attempt to discredit the open-access (OA) movement altogether, or that discussion of predatory journals draws attention away from systemic issues in traditional scholarly publishing [ 20 - 22 ]. Other commentators have noted that the language and tools used to discuss and assess predatory journals is racially biased, and discriminates against newer journals, journals from developing countries, and journals from non-English-speaking countries [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%